The Effect of Role Playing Learning Model on Students Historical Empathy at SMA Negeri 1 Bayah: Pengaruh Model Pembelajaran Role Playing terhadap Empati Sejarah Siswa di SMA Negeri 1 Bayah - Tubagus Umar Syarif Hadi Wibowo; Ana Nurhasanah; Dian Ami Astuti (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to determine the effect of role playing learning model on historical empathy of class XI SMA Negeri 1 Bayah students. The method used was quasi experiment with non equivalent control group design. The research sample consisted of XI-4 (experimental) and XI-6 (control) classes. Data were collected through pre test and post test using historical empathy questionnaire. The results of the independent sample t-test showed a significant difference between the experimental and control groups (p = 0.042), which means that the role playing model is effective in increasing students' historical empathy.